IQGAP Family Members in Yeast, Dictyostelium, and Mammalian Cells - Katie B. Shannon (International Journal of Cell Biology)
IQGAPs are a family of scaffolding proteins with multiple domains, named for the IQ motifs and GTPase activating protein (GAP) related domains. Despite their GAP homology, IQGAP proteins act as effectors for GTP-bound GTPases of the Ras superfamily and do not stimulate GTP hydrolysis. IQGAPs are found in eukaryotic cells from yeast to human, and localize to actin-containing structures such as lamellipodia, membrane ruffles, cell-cell adhesions, phagocytic cups, and the actomyosin ring formed during cytokinesis. Mammalian IQGAPs also act as scaffolds for signaling pathways. IQGAPs perform their myriad functions through association with a large number of proteins including filamentous actin (F-actin), GTPases, calcium-binding proteins, microtubule binding proteins, kinases, and receptors. The focus of this paper is on recent studies describing new binding partners, mechanisms of regulation, and biochemical and physiological functions of IQGAPs in yeast, amoeba, and mammalian cells.